DEFORMATION INTERACTION OF STRONG EARTHQUAKES OF 2010–2016 IN THE ZONE OF INFLUENCE OF THE HIKURANGA SUPERPLUME (NEW ZEALAND) ACCORDING TO GPS OBSERVATIONS - V. I. Kaftan; P. A. Dokukin; A. I. Manevich; V. N. Tatarinov; R. V. Shevchuk (Геодинамика и тектонофизика)
Between 2010 and 2016, a series of 11 strong M>6 earthquakes occurred in New Zealand. In the area covering the epicentral zones of these seismic events, the spatiotemporal characteristics of movements and deformations of the Earth’s crust were obtained based on the processing of continuous satellite GPS observations at 64 points of the geodetic network. Using these data, we have studied the evolution of horizontal movements and deformations in order to reveal the possible relationship between the observed deformational and seismic processes. Analysis has been made on the total shear deformation, since the main tectonic structures of the region are faults with a shear mechanism of displacement of their sides. The presence of a giant mantle superplume in the area was the reason for the study of the behavior of horizontal dilatation deformation, and horizontal and vertical crustal motions. Based on the obtained digital deformation models, there were created kinematic visualizations, which are synoptic animations providing direct observations of the seismic deformation process and their heuristic analysis. The study revealed that a series of the strongest earthquakes may be interconnected by a long-term single deformation process, which is caused by the occurrence of an anomalous total shear deformation. The general maximum of shear deformation, dilatation deformation, and horizontal and vertical displacements are concentrated in the center of mantle superplume activity. Prior to strong seismic events, there occur zones of deficit (minimum) displacements of the Earth’s crust in the area of future epicenters, which is of research interest in terms of predicting their locations.